Problems of education of the younger generation of national identity in the works of Shevchenko and Hrinchenko - Тарнавський А. (Видавничо-поліграфічний центр "Київський університет", 2014)
This paper addresses the problem of education of the younger generation of identity in the works of T. Shevchenko and B.D. Hrinchenkо.

Розглядаються проблеми виховання самосвідомості молодого покоління у творах Т.Г. Шевченка та Б.Д. Грінченка.
Проблеми виховання національної самосвідомості молодого покоління у творах Шевченка та Грінченка
Keywords: education; identity; youth; Shevchenko; Hrinchenko; виховання; самосвідомість; молодь; Шевченко; Грінченко